INFLUENCE OF MOTIVATION, SELF EFFICACY AND CAREER EXPECTATIONS TOWARDS COMMITMENT TO BE ECONOMICS TEACHERS - khasan setiaji (Fakultas Ekonomi Universitas Negeri Jakarta, 2018)
Career commitment becomes an important thing for education students to survive on their career choice, considering that the students have just entered the first stage of career to become a teacher that is the preservice stage. This aim study is to determine the effect of motivation to become a teacher, self efficacy, and teaching career expectation partially or simultaneously to UNNES students of Economics Education department. This study used quantitative approach with analysis methods used multiple linear regression analysis. The study result showed that partially, motivation to become a teacher affected commitment career to be a teaching at 4.36%, self-efficacy affected commitment career to be a teaching at 4.49%, and teaching career expectation affected commitment career to be a teaching at 25.80%. Simultaneously, motivation to become a teacher, self-efficacy, and teaching career expectation affected commitment career to be a teaching at 33.8%. It can be concluded that an effect of motivation to become a teacher, self-efficacY, AND TEACHING CAREER EXPECTATION ON COMMITMENT CAREER TO BE A TEACHER TO UNNES STUDENTS OF ECONOMICS EDUCATION DEPARTMENT. BY PARTIALLY AND SIMULTANEOUSLY